(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Al-Farabi is the founder of eastern peripatetism. His multifaceted heritage synthesized in itself Islamic spirituality and antique rationalism. In this connection, we can say that al-Farabi defined the essence and importance of Islamic rationality. The legacy of the philosopher from Otrar was become popular in the XIXth century. Leaders of Islamic reformation used al-Farabi’s ideas. They attempted withdraw from backward Muslim community and create optimal balance between Islam and European scientific, socio-cultural, technological achievements. The main objective of the research is to identify concept of equivalence between faith and mind, religion and philosophy formulated by al-Farabi in the works of Muslim reformers. The basis of methodology in this research was genetic method revealed by Russian philosopher, psychologist, and follower of Russian Neokantianism A.I. Vvedensky. Scientific novelty of the research is the identification and designation al-Farabi’s ideas in the works of Muslim reformers from India, Egypt, and Afghanistan and in the heritage of Tatar reformers. Key words: аl-Farabi, Muslim Reformation, Tradition, Innovation.